2020
DOI: 10.3174/ajnr.a6633
|View full text |Cite
|
Sign up to set email alerts
|

Lower Lactate Levels and Lower Intracellular pH in Patients with IDH-Mutant versus Wild-Type Gliomas

Abstract: BACKGROUND AND PURPOSE: Preclinical evidence points toward a metabolic reprogramming in isocitrate dehydrogenase (IDH) mutated tumor cells with down-regulation of the expression of genes that encode for glycolytic metabolism. We noninvasively investigated lactate and Cr concentrations, as well as intracellular pH using 1 H/phosphorus 31 ( 31 P) MR spectroscopy in a cohort of patients with gliomas.MATERIALS AND METHODS: Thirty prospectively enrolled, mostly untreated patients with gliomas met the spectral quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 58 publications
2
5
0
Order By: Relevance
“…In this study, we discovered that the unsupervised clustering with LMG expression signature could stratify glioma samples into two consensus clusters, in which one was associated with IDH wildtype gliomas and was more likely to have a more sophisticated and immunosuppressive microenvironment. This result was consistent with the findings reported by Wenger et al that the higher level of glycolysis in the IDH wild type gliomas was associated with more lactate in TME, which could potentially disturb the distribution and functionality of immune cells (8).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this study, we discovered that the unsupervised clustering with LMG expression signature could stratify glioma samples into two consensus clusters, in which one was associated with IDH wildtype gliomas and was more likely to have a more sophisticated and immunosuppressive microenvironment. This result was consistent with the findings reported by Wenger et al that the higher level of glycolysis in the IDH wild type gliomas was associated with more lactate in TME, which could potentially disturb the distribution and functionality of immune cells (8).…”
Section: Discussionsupporting
confidence: 93%
“…Despite the massive research investment and clinical experiments reported worldwide, the treatment of glioma has not yet to be revolutionized and the prognosis of glioma patients is not ideal, causing loss of quality of life (QOL) and financial stress for patients and their family ( 38 , 39 ). Lactate is one of the components in the TME, whose concentration has been associated with the molecular features and prognosis of gliomas ( 8 ). Meanwhile, lactate metabolism has been considered to regulate tumor immunity through diverse mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, lactate levels are significantly increased in IDH wt gliomas. In contrast, IDH mutant cells exhibit reduced hyperpolarized lactate production along with decrease of LDH as well as MCT1 and MCT4 levels [ 120 , 121 , 122 , 123 ].…”
Section: The Acidic Tumor Microenvironment In Idh Wt Versus Idh Mutant Gliomasmentioning
confidence: 99%
“…These results showed indications of faster cell reproduction in MGMT-methylated and EGFR-amplified tumors and higher apoptotic activity in EGFR-amplified tumors regardless of the MGMT-status [62]. Another study showed lower lactate levels and intracellular pH in IDH-mutant gliomas compared to IDH-wild type gliomas [63]. However, other 31P-MRS markers were not significantly altered and could not predict the IDH-mutation status [64].…”
Section: Future Aspects and 31p-mrsmentioning
confidence: 93%